2012
DOI: 10.1007/s11252-012-0250-7
|View full text |Cite
|
Sign up to set email alerts
|

Conifer growth and reproduction in urban forest fragments: Predictors of future responses to global change?

Abstract: Global change has a large and growing influence on forests, particularly in urban and urbanizing areas. Compared to rural forests, urban forests may experience warmer temperatures, higher CO 2 levels, and greater nitrogen deposition, with exacerbated differences at urban forest edges. Thus, comparing urban to rural forests may help predict future effects of global change on forests. We focused on the conifer western red-cedar (Thuja plicata) to test three hypotheses: at urban forest edges, relative to rural fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…Another study along a rural-urban gradient in Baltimore showed that ecosystem productivity in secondary succession fields increased 60% and 115% for the suburban and urban sites, respectively, relative to the rural site (5). Growth enhancement in urban settings has also been reported in the conifer western red cedar (Thuja plicata) in Seattle (21) and in pine and oak forests in the Florida Panhandle (22). These isolated field studies corroborated our findings from remote sensing that enhancement of the EVI is overwhelmingly positive across cities.…”
Section: Urbanization Effects On Vegetation Growth: Evidence From Directmentioning
confidence: 90%
“…Another study along a rural-urban gradient in Baltimore showed that ecosystem productivity in secondary succession fields increased 60% and 115% for the suburban and urban sites, respectively, relative to the rural site (5). Growth enhancement in urban settings has also been reported in the conifer western red cedar (Thuja plicata) in Seattle (21) and in pine and oak forests in the Florida Panhandle (22). These isolated field studies corroborated our findings from remote sensing that enhancement of the EVI is overwhelmingly positive across cities.…”
Section: Urbanization Effects On Vegetation Growth: Evidence From Directmentioning
confidence: 90%
“…For example, in urban forested natural areas in Seattle, Washington, logging and the selective removal of old‐growth trees, which contribute a disproportionate amount of total seed within populations, have been hypothesized to drive local source limitation and limit natural regeneration of conifer species (O'Brien et al . ; Ettinger et al . ).…”
Section: Evidence Of Urban Plant Recruitment Limitationmentioning
confidence: 99%
“…Edge effects, human activity, and soil contamination are just a few of the many urban drivers that may limit plant growth and survival (eg O'Brien et al . ; Pregitzer et al . ).…”
Section: Evidence Of Urban Plant Recruitment Limitationmentioning
confidence: 99%
See 2 more Smart Citations